Adeno-associated viruses (AAV) - Berns, Kenneth (Henry Stewart Talks, 2007)
Adeno-associated virus, Molecular biology, Persistent infection, Lack of pathogenicity, Use as a vector for gene therapy, Vector structure and properties, Vector production, Clinical trials
Archived at 2017/09/14